2020
DOI: 10.1111/febs.15604
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term protein restriction at advanced age stimulates FGF21 signalling, energy expenditure and browning of white adipose tissue

Abstract: A reduced dietary protein intake has been demonstrated to improve metabolic health under various conditions. Here, it is shown that a short‐term 7% low‐protein dietary intervention can impact age‐related metabolic health in 18‐month‐old animals. Alongside increased plasma fibroblast growth factor 21 levels, a low‐protein diet induces energy expenditure and browning of white adipose tissue in 18‐month‐old mice, without negatively affecting muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…Although hepatic FGF21 seems to stimulate BAT thermogenesis via an endocrine pathway ( 29 , 30 , 36 , 74 , 89 ), the FGF21 expression and secretion in BAT is also increased by sympathetic stimulation ( 72 , 90 ). We and others showed that plasma FGF21 concentrations and transcripts in liver, small intestine, skeletal muscle and BAT were increased when rodents are fed with low protein diets ( 27 , 31 , 36 , 53 , 60 , 75 , 91 ). Further, methionine and leucine restriction increases FGF21 expression particularly in liver and circulation ( 92 94 ).…”
Section: Regulation Of Energy Expenditure By Low Protein Dietsmentioning
confidence: 89%
See 3 more Smart Citations
“…Although hepatic FGF21 seems to stimulate BAT thermogenesis via an endocrine pathway ( 29 , 30 , 36 , 74 , 89 ), the FGF21 expression and secretion in BAT is also increased by sympathetic stimulation ( 72 , 90 ). We and others showed that plasma FGF21 concentrations and transcripts in liver, small intestine, skeletal muscle and BAT were increased when rodents are fed with low protein diets ( 27 , 31 , 36 , 53 , 60 , 75 , 91 ). Further, methionine and leucine restriction increases FGF21 expression particularly in liver and circulation ( 92 94 ).…”
Section: Regulation Of Energy Expenditure By Low Protein Dietsmentioning
confidence: 89%
“…Likewise, others have shown that low protein induced EE occurs independent of hyperphagia ( 35 ) and that energy intake changes as a secondary response to compensate for the enhanced EE ( 70 ). Therefore, it appears that increased EE in response to protein restriction is partly related to enhanced basal metabolic rate component of total EE ( 53 ), although the contribution of basal metabolic rate and diet-induced thermogenesis was reported to be negligible ( 71 ). An increased spontaneous motor activity was reported in mice fed with low protein diets ( 71 ), which does not seem to be related with the overall activity level ( 69 , 71 ).…”
Section: Regulation Of Energy Expenditure By Low Protein Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A: detailed timeline. Energy expenditure (EE), respiratory exchange ratio (RER) and measurements from blood samples were performed as described elsewhere (22).…”
Section: Introductionmentioning
confidence: 99%